A distributed soil temperature measurement system with high spatial resolution based on BOTDR - Gao, Lei; Shi, Bin; Zhu, Youqun; Wang, Ke; Sun, Yijie; Tang, Chaosheng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
This paper presents a new, recently developed, distributed soil temperature measurement sensor system, with high spatial resolution, based on Brillouin optical time domain reflectometry (BOTDR). The process of developing the distributed soil temperature sensor is introduced in detail, including the principle, materials, installation, instrumentation and calibration. The new distributed soil temperature sensor improves the spatial resolution from 100 cm to 3.3 cm, and has some other unique advantages, including long distance measurement capability, a longer life cycle, galvanic isolation, EMI immunity, good stability and ease of integration. Finally, an in situ comparison test was carried out, where results from the new sensor were compared to data measured using a standard point-mode system. This test proves that the newly developed distributed sensor is both accurate and has the capability to measure continuously the distribution of the soil temperature along the whole borehole depth, indicating that this new measure technique has a wide and powerful application potential.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 607-616
Keywords: optyka; distributed temperature measurement; Brillouin optical time domain reflectometry (BOTDR); high spatial resolution; soil temperature